ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA BIDANG PERHUBUNGAN DARAT PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN TAKALAR - Ambo Masse S.Sos.M.Si; Dr. Abdul Sahid Ilyas, M.Si (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
This research was conducted at the Office Tranportastion Depatment in Takalar Regency. This research has the character of which gives description and clarification concerning strategy of human resource development at Transportation Department in Takalar Regency, and also factors pursuing strategy of human resource development at Transportation Department in Takalar Regency. The basic of research was survey approach. This research aim to know the strategy of human resource development and also factors pursuing strategy of human resource development in Transportation Departemen in Takalar Regency. This research used saturated samples all population at become sample. The conclusion of this research that namely strategy of human resource depelopment in Transportation Department in Takalar Regency was through formal education, training and officer. Execution of officer location in Transportation Department in Takalar Regency was during the time assumed less compatible. Factors pursuing strategy of human resource development in Transportation Department in Takalar Regency consisted of the resistance eksternal covering legislation change, and political area growth. While internal resistance include the plan strategy which not precise of the goals, organization structure which centralistic and mecanistic, technology growth which quickly, and also finite budget.